2017
DOI: 10.18632/oncotarget.14432
|View full text |Cite
|
Sign up to set email alerts
|

Folate intake, serum folate levels and esophageal cancer risk: an overall and dose-response meta-analysis

Abstract: Previously reported findings on the association between folate intake or serum folate levels and esophageal cancer risk have been inconsistent. This study aims to summarize the evidence regarding these relationships using a dose-response meta-analysis approach. We performed electronic searches of the Pubmed, Medline and Cochrane Library electronic databases to identify studies examining the effect of folate on the risk of esophageal cancer. Ultimately, 19 studies were included in the meta-analysis. Summary odd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 43 publications
3
30
0
Order By: Relevance
“… NS Tio [ 52 ] 36 studies. Breast Dietary folate NS: once adjusted 608,265 sample size, 34,602 cases Total folate intake NS Menopausal status NS once adjusted Hormone status NS Study design S: retrospective study design showed decreased risk of postmenopausal breast cancer Fan C [ 18 ] 4,090/10,902 9 case-control studies: 7 dietary folate with FFQ; 2 studies serum folate concentration; 4 studies dose-response analysis Head and neck Folate intake S: decreased risk comparing highest to lowest folate intake Dose-response S: every 100 mcg/day increase in folate intake associated with 4.3% decreased risk Galeone C [ 19 ] 5,127/13,249 Pooled analysis of individual-level data from 10 case-control studies Oral cavity and pharyngeal (OPC) Total folate intake S: Reduced risk for highest compared lowest quintile total folate intake and overall OPC risk S: decreased risk for oral cavity Alcohol S: increased risk for heavy drinkers with low folate intake compared to low alcohol intake with higher folate intake Smoking S: increased risk for smoking Zhao Y [ 20 ] 19 studies Esophageal Dietary folate intake S: decreased risk with highest folate intake compared to lowest intake 14 case-control 1 cohort dietary folate intake 6 case-control 1 cohort for dose-response Dose-response S: 100 mcg/day increment in dietary folate intake reduced risk by 12% Tio M [ 21 ] 9 case-control 2574/9254 for any histological type of esophageal cancer. Esophageal, gastric, pancreatic Dietary folate S: dietary folate associated with decreased risk of esophageal and pancreatic cancer NS: gastric cancer 8 studies (5 prospective, 3 retrospective) 2209/295,526 for pancreatic cancer.…”
Section: Methodsmentioning
confidence: 99%
“… NS Tio [ 52 ] 36 studies. Breast Dietary folate NS: once adjusted 608,265 sample size, 34,602 cases Total folate intake NS Menopausal status NS once adjusted Hormone status NS Study design S: retrospective study design showed decreased risk of postmenopausal breast cancer Fan C [ 18 ] 4,090/10,902 9 case-control studies: 7 dietary folate with FFQ; 2 studies serum folate concentration; 4 studies dose-response analysis Head and neck Folate intake S: decreased risk comparing highest to lowest folate intake Dose-response S: every 100 mcg/day increase in folate intake associated with 4.3% decreased risk Galeone C [ 19 ] 5,127/13,249 Pooled analysis of individual-level data from 10 case-control studies Oral cavity and pharyngeal (OPC) Total folate intake S: Reduced risk for highest compared lowest quintile total folate intake and overall OPC risk S: decreased risk for oral cavity Alcohol S: increased risk for heavy drinkers with low folate intake compared to low alcohol intake with higher folate intake Smoking S: increased risk for smoking Zhao Y [ 20 ] 19 studies Esophageal Dietary folate intake S: decreased risk with highest folate intake compared to lowest intake 14 case-control 1 cohort dietary folate intake 6 case-control 1 cohort for dose-response Dose-response S: 100 mcg/day increment in dietary folate intake reduced risk by 12% Tio M [ 21 ] 9 case-control 2574/9254 for any histological type of esophageal cancer. Esophageal, gastric, pancreatic Dietary folate S: dietary folate associated with decreased risk of esophageal and pancreatic cancer NS: gastric cancer 8 studies (5 prospective, 3 retrospective) 2209/295,526 for pancreatic cancer.…”
Section: Methodsmentioning
confidence: 99%
“…In mammals, the vitamin folate is a key source of the one carbon group used to methylate DNA, DNA methylation is an epigenetic modification critical to normal genome regulation and development (11). So the biological function of folate and FHIT suggest that influence of folate to cervical carcinogenesis may be associated with the activity and function of FHIT gene, poor folate status may contribute to CC risk through effects on one-carbon metabolism and DNA methylation (38) there is enormous interest in assessing the potential for changes in folate intake to modulate DNA methylation as a mechanistic link to cancer. Research in rat liver showed a significant 20% decrease in genomic DNA methylation associated with a severe degree of dietary folate deficiency of 4 weeks' duration (39).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, dietary factors [7] may affect the risk of esophageal cancer. Previous studies suggested that vitamins intake [8,9], fiber intake [10], folate intake [11,12], could decrease the development of esophageal cancer. Intakes of bioactive compounds from various plant sources also reduced the risk of cancer [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%